Investigating the role of Hsp90 and LRP1 in FN matrix dynamics - Boël, Natasha Marie-Eraine (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2016)
Fibronectin (FN), a matrix protein responsible for regulating processes including migration and differentiation, is secreted as a soluble dimer which is assembled into an insoluble extracellular matrix. The dynamics of FN matrix assembly and degradation play a large role in cell migration and invasion contributing to the metastatic potential of cancer cells. Previous studies from our group have shown the direct binding of Hsp90 and FN in vitro and that inhibition of Hsp90 with novobiocin (NOV) caused internalisation of the FN matrix. However, the receptor mediating this internalisation is currently unknown. Low density lipoprotein 1 (LRP1) is a likely candidate as it is a ubiquitous receptor responsible for regulating internalisation of diverse ligands and is known to bind both Hsp90 and FN. We used wild type and knockout LRP1 cell lines to study the endocytosis of FN via this receptor. Here, we demonstrate that LRP1-deficient cells accumulated greatly increased levels of FN and were found to be less sensitive to pharmacological inhibition of Hsp90 by NOV. LRP1-expressing MEF-1 and Hs578T breast cancer cells experienced an increase in total FN in response to NOV, at concentrations below the EC50 value, followed by a dose-dependent loss of FN. We attributed greater FN levels to a loss of extracellular FN matrix coupled with increased internalisation of FN. Cell-surface biotinylation and DOC assays showed that loss of extracellular FN was specific to LRP1-expressing MEF-1 cells. Furthermore, we demonstrate that the loss of extracellular FN is not affected by changes in FN mRNA levels as determined by qRT-PCR, and that treatment with NOV resulted in the accelerated degradation of FN in the presence of cycloheximide. Immunoprecipitation studies reveal a putative complex exists between FN, Hsp90 and LRP1 in both cancer and non-cancer cells which is not perturbed by NOV. Western analyses revealed increased proteolytic processing of LRP1 in response to NOV which we proposed, based on literature, to modulate signalling pathways as a potential mechanism for regulating FN turnover. Moreover, using wound healing assays we identified increased migration to be one of the consequences associated with loss of extracellular FN by Hsp90 inhibition but only in cells containing LRP1. In summary, this study provides new insights into the Hsp90-LRP1 mediated loss of FN matrix and also reveals for the first time the functional consequence related to FN turnover by NOV was an increase in migration in LRP1-expressing cells.
Keywords: Extracellular matrix; Molecular chaperones; Heat shock proteins; Cancer; Fibronectins